Anti-NMDA Receptor Encephalitis Masquerades as Psychosis: A Case Report. Issue 1 (January 2022) - Giri, Yam R.; Korie, Ijendu; Hashmi, Seema; Parrill, Allison; Ayed, Nisrin
Abstract : A 28-year-old male patient with an unclear history of psychosis was admitted to the inpatient psychiatric unit. He presented with auditory hallucinations, agitation, and bizarre and disorganized behavior. He was treated with antipsychotic medications without improvement. Magnetic resonance imaging of the brain showed hyperintensities throughout the brain parenchyma. Investigations for infectious, metabolic, autoimmune, and malignant etiologies were negative. Anti–N-methyl-D-aspartate (NMDA) receptor encephalitis was suspected. Cerebrospinal fluid (CSF) and serum NMDA receptor antibody testing were performed. Both tests were positive, confirming anti-NMDA receptor encephalitis. The patient was treated with intravenous immunoglobulin and methylprednisolone, which resulted in the resolution of his psychosis. In the case of unexplained psychosis associated with seizures, early screening using serum and CSF testing for anti-NMDA receptor antibodies and brain magnetic resonance imaging may be an important diagnostic tool for detecting anti-NMDA receptor encephalitis. Detailed investigations of CSF and serum should be performed to rule out infectious, metabolic, and autoimmune causes. Imaging studies should also be performed to identify any tumors such as a teratoma. This approach may help identify patients with anti-NMDA receptor encephalitis masquerading as psychosis. Early diagnosis and treatment including intravenous steroids, immunosuppressants, plasmapheresis, and removal of any teratoma if present in patients with anti-NMDA receptor encephalitis can improve the overall outcome.